Effect of Number of Zones on Subjective Vision in Concentric Bifocal Optics - Legras, Richard; Rio, David (Optometry and vision science, 2015)
PURPOSETo evaluate the influence of the number of concentric zones of a center-near bifocal optics on the subjective quality of vision. METHODSTwenty-two subjects scored with a five-item continuous grading scale the quality of vision of calculated images (i.e., three high-contrast 20/50 letters) viewed through their best sphero-cylindrical correction and a 3-mm pupil to limit the impact of their aberrations. Through-focus images were calculated from −4 to +2 diopters (D), each 0.25 D, in the presence of center-near bifocal optics (Add 2.5 D) varying by their number of concentric zones (from 2 to 20). RESULTSTo compare the results obtained with these profiles, we calculated the area under the (through-focus) curve (AUC) higher than 2 out of 5 (i.e., limit between a poor and a fair image quality, considered as the limit of acceptability). This value was normalized by the naked eye condition and divided into distance, intermediate, and near AUC. The results showed large interindividual variations. Distance AUC remained quite similar whatever the profile, near AUC decreased with the number of concentric zones, and intermediate AUC rose with the number of concentric zones. With 10 and 20 concentric zones, diffraction phenomenon induced constructive interferences at intermediate proximities and destructive interferences at distance and near proximities. CONCLUSIONSTo balance distance, intermediate, and near quality of vision, a number of zones between 8 and 10 should be chosen. If the subject does not need intermediate quality of vision, then a profile with two to five zones should be favored.